Measurement of the absolute branching fraction of D+ → K̅0 e+νe via K̅0 → π0π0*Supported by National Key Basic Research Program of China (2009CB825204, 2015CB856700), National Natural Science Foundation of China (NSFC) (10935007, 11125525, 11235011, 11305180, 11322544, 11335008, 11425524, 11475123), Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, CAS Center for Excellence in Particle Physics (CCEPP), Collaborative Innovation Center for Particles and Interactions (CICPI), Joint Large-Scale Scientific Facility Funds of NSFC and CAS (11179007, U1232201, U1332201, U1532101), CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS, National 1000 Talents Program of China, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG (Collaborative Research Center CRC-1044), Istituto Nazionale di Fisica Nucleare, Italy, Koninklijke Nederlandse Akademie van Wetenschappen (KNAW) (530-4CDP03), Ministry of Development of Turkey (DPT2006K-120470), National Natural Science Foundation of China (NSFC) (11405046, U1332103), Russian Foundation for Basic Research (14-07-91152), Swedish Resarch Council, U. S. Department of Energy (DE-FG02-04ER41291, DE-FG02-05ER41374, DE-SC0012069, DESC0010118), U.S. National Science Foundation, University of Groningen (RuG) and Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (November 2016) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Baldini Ferroli, R.; Ban 班, Y. 勇; et al.
Abstract: By analyzing 2.93 fb −1 data collected at the center-of-mass energy with the BESIII detector, we measure the absolute branching fraction of the semileptonic decay D + → K̅ 0 e + νe to be ℬ( D + → K̅ 0 e + νe ) = (8.59 ± 0.14 ± 0.21)% using, where the first uncertainty is statistical and the second systematic. Our result is consistent with previous measurements within uncertainties..